Boundary layer sources for the Asian anticyclone: Regional contributions to a vertical conduit. Issue 6 (28th March 2013) - Bergman, John W.; Fierli, Federico; Jensen, Eric J.; Honomichl, Shawn; Pan, Laura L.
Abstract: [1] The transport of air from the planetary boundary layer (PBL) into the Asian Summer Monsoon anticyclone is investigated using backward trajectories initiated within the anti‐cyclone at 100 mb and 200 mb during August 2011. Transport occurs through a well‐defined conduit centered over the southern Tibetan plateau, where convection lofts air parcels into the anticyclone. The conduit, as a dynamical feature, is distinct from the anticyclone. Thus, while the anticyclone influences transport through the upper troposphere and lower stratosphere, it does not by itself define a transport pipeline through that region. To quantify model sensitivities, parcel trajectories are calculated using wind fields from multiple analysis data sets (European Centre for Medium‐Range Weather Forecasts, National Center for Environmental Prediction's Global Forecasting System, and NASA's Modern‐Era Retrospective Analysis for Research and Applications [MERRA]) and from synthetically modified data sets that explore the roles of vertical motion and horizontal resolution for discrepancies among these calculations. All calculations agree on the relative contributions to PBL sources for the anticyclone from large‐scale regions with Tibetan Plateau and India/SE Asia being the most important. However, they disagree on the total fraction of air within the anticyclone that was recently in the PBL. At 200 mbar, calculations using MERRA are clear outliers due to problematic vertical motion in those data. Large differences among the different data sets at 100 mbar are more closely related to horizontal resolution. It is speculated that this reflects the importance of deep, small‐scale convective updrafts for transport to 100 mbar. Key Points: Air transport to the Asian anticyclone is confined to a vertical conduit Regional contributions to anticyclone are robust Vertical motion explains discrepancies in total fraction of young air